Oil price shocks and real GDP growth: empirical evidence for some OECD countries - Rebeca Jiménez-Rodríguez; Marcelo Sánchez (European Central Bank (ECB), 2004)
This paper assesses empirically the effects of oil price shocks on the real economic activity of the main industrialised countries. Multivariate VAR analysis is carried out using both linear and nonlinear models. The latter category includes three approaches employed in the literature, namely, the asymmetric, scaled and net specifications. We find evidence of a non-linear impact of oil prices on real GDP. In particular, oil price increases are found to have an impact on GDP growth of a larger magnitude than that of oil price declines, with the latter being statistically insignificant in most cases. Among oil importing countries, oil price increases are found to have a negative impact on economic activity in all cases but Japan. Moreover, the effect of oil shocks on GDP growth differs between the two oil exporting countries in our sample, with the UK being negatively affected by an oil price increase and Norway benefiting from it.
Keywords: E32; Q43; 330; Macroeconomic fluctuations; Non-linear models; Oil price shock; Ölpreis; Wirtschaftswachstum; G7-Staaten; EU-Staaten; Norwegen